Contribution of Self Efficacy and Social Support to Teachers' Readiness to Face Retirement - Sri Hariyati; Mudjiran Mudjiran; Daharnis Daharnis (Jurnal Aplikasi IPTEK Indonesia, 2020)
This study aims to describe and analyze self-efficacy, social support, and teacher readiness to face retirement. The research was carried out using descriptive quantitative methods. The population of this research is 125 teachers who will retire in Kecamatan Bangkinang Kota, Riau, and the research sample is 95 teachers who will retire in Kecamatan Bangkinang Kota, Riau. Sampling using a purposive sampling technique. The research data were analyzed using simple regression and multiple regression. The data analysis process uses the help of the SPSS program. The findings of this study are: (1) self-efficacy contributes to teacher readiness to face retirement with an effective contribution of 28.1%, (2) social support contributes to teacher readiness to face retirement by 21.6% (3) self-efficacy and social support simultaneously. collectively contributed 31.5% to teachers' readiness to face retirement. The implications of the results of this study can be used as a basis for the preparation of guidance and counseling service programs.